Constrained output tracking control for time-varying bilinear systems via RHC with infinite prediction horizon - Phuoc, Nguyen Doan; Ha, Le Thi Thu (Journal of Computer Science and Cybernetics, 2015)
The paper introduces an algorithm to design a feedback controller, which guarantees the tracking of time varying bilinear system outputs for desired values in the presence of input constraint. The proposed controller employs the ideas of receding horizon principle and constrained optimal control. A theorem for the tracking stability of closed loop system is given. An updated law of weighting matrices in the cost function to keep the input constraint condition is also proposed. Finally, the tracking behavior of the closed loop system is illustrated through a numerical example.